Comparison on online shopping apps: a study conducted on smartphone users of West Bengal. (9th August 2019) - Chakraborty, Debarun
"I love ordering things online for my purchase because when they arrive it is a present to me from me". This freaky quote is definitely a manifestation of the current shopping behaviour which frames around the buzzword 'online shopping' and 'e-commerce'. In both marketing quarter of the corporate houses and the academic quarter as well online shopping is getting a momentum at a steady accelerated pace and its well reflected in the shopping habits of the Indian urban folk. The promising growth of online shopping in India is indeed prompting factor to take up the research study where preferred online shopping portals are compared and contrasted on selected parameters to ascertain which of those the most is sought after by the shoppers. The study was conducted in the eastern metropolis like Kolkata as well as in Siliguri, Durgapur and Asansol. The research design was a cross sectional study. The relevant Chi square method was employed to find out the best shopping site compared to the rest of the sites selected.